Treatment-refractory ALK-positive inflammatory myofibroblastic tumour of the oral cavity. (11th April 2018) - LaVigne, Anna W; Meredith, David M; D'Adamo, David R; Margalit, Danielle N
Abstract : We present a challenging case of a previously healthy 23-year-old man who developed an inflammatory myofibroblastic tumour of the hard palate, harbouring a rearrangement of the anaplastic lymphoma kinase (ALK) locus. Despite surgical intervention, radiotherapy and ALK-inhibition therapy, the tumour recurred locally and metastasised to regional lymph nodes, and the patient passed away roughly 9 months after diagnosis from local progression. The rapid progression of this patient's disease and its resistance to treatment demonstrate the potentially aggressive clinical course of inflammatory myofibroblastic tumours. ALK-inhibition therapy was unsuccessful in this ALK-positive tumour, highlighting the need for further investigation of markers predictive of disease progression and treatment response.